2002
DOI: 10.1093/emboj/21.10.2496
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the tetrameric Mad1-Mad2 core complex: implications of a 'safety belt' binding mechanism for the spindle checkpoint

Abstract: The spindle checkpoint protein Mad1 recruits Mad2 to unattached kinetochores and is essential for Mad2–Cdc20 complex formation in vivo but not in vitro. The crystal structure of the Mad1–Mad2 complex reveals an asymmetric tetramer, with elongated Mad1 monomers parting from a coiled‐coil to form two connected sub‐complexes with Mad2. The Mad2 C‐terminal tails are hinged mobile elements wrapping around the elongated ligands like molecular ‘safety belts’. We show that Mad1 is a competitive inhibitor of the Mad2–C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
450
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(483 citation statements)
references
References 47 publications
(110 reference statements)
27
450
0
Order By: Relevance
“…Both solution and crystal structures of Mad2 in association with this motif have been solved (Luo et al, 2002;Sironi et al, 2002). Mad1 binding to Mad2 induces the same conformational changes in Mad2 as does the Cdc20 peptide (Luo et al, 2002;Sironi et al, 2002). Thus, Cdc20 and Mad1 binding to Mad2 are mutually exclusive.…”
Section: Role Of Mad1mentioning
confidence: 99%
“…Both solution and crystal structures of Mad2 in association with this motif have been solved (Luo et al, 2002;Sironi et al, 2002). Mad1 binding to Mad2 induces the same conformational changes in Mad2 as does the Cdc20 peptide (Luo et al, 2002;Sironi et al, 2002). Thus, Cdc20 and Mad1 binding to Mad2 are mutually exclusive.…”
Section: Role Of Mad1mentioning
confidence: 99%
“…It has been shown that Mad2, a protein whose interaction with the APC/C activator Cdc20 is essential for the mitotic checkpoint in vivo (10,11) and inhibits the activity of APC/C Cdc20 in vitro (12,13). Mad2 exists in two conformations, of which the closed conformer preferentially binds Cdc20 (14,15). Elegant models have been proposed according to which the activation of the checkpoint promotes binding of Cdc20 to the closed conformer of Mad2 and thus sequesters Cdc20 from APC/C (refs.…”
mentioning
confidence: 99%
“…Moreover, f luorescence recovery after photobleaching (FRAP) experiments have revealed that some of these proteins, including Mad2, BubR1, and Cdc20, turnover rapidly at unattached kinetochores (6,9). Furthermore, the available evidence suggests that Mad2 exists in two forms: open (O-Mad2) and closed (C-Mad2) (10,11), with the closed form adopted when bound to Cdc20. Production of C-Mad2-Cdc20 may be catalyzed by the kinetochorebound C-Mad2-Mad1 complex.…”
mentioning
confidence: 99%